Afrontamiento al estrés y depresión en aspirantes a policía a la Escuela de Formación de policías de línea GOE-Guano, periodo diciembre 2016 - mayo 2017 - Pozo Cárdenas, Jonathan Patricio (2017)
This research project entitled "STRESS-TO-STRESS AND DEPRESSION IN POLICE ASPIRENTS TO THE GOE-GUANO LINE POLICE TRAINING SCHOOL, PERIOD DECEMBER 2016-MAY 2017" aims to: analyze coping with stress in the depression to the Aspirants of formation of Police of line GOE-Guano school. The design of the research is transversal using a quantitative approach, making use of a field research and bibliographical, the level of research is descriptive. The chosen population was conformed by 80 aspirants to police and through criterion of inclusion and exclusion a sample of 30 aspirants has been selected. The chosen data collection techniques and instruments have been: the Lazarus Coping Mode Scale and the Beck Depression Inventory (BDI-II). Among the most important results it has been found that 53.3% of the applicants use the same mode of coping and that 73.3% indicate that they have depression. Therefore, it is concluded that the modes of coping with stress have an impact on the development of depression within the aspirants to the police force. At the end of this research project, strategies have been proposed for the adequate management of coping with stress and depression so that aspiring police officers can adequately conclude their training and be a great contribution within society.